Properties of water hyacinth fibers (Eichhornia crassipes) filled low density polyethylene/acrylonitrile butadiene styrene composites - Ahmed Saleem, Oleiwi Al-Khuzaie (Universiti Malaysia Perlis, 2011)
The water hyacinths are largely available in local rivers. In this research, the water hyacinth fibers have been used as reinforcing components for low density polyethylene (LDPE) and acrylonittile butadiene styrene (ABS). The chemical treatment using Isophorone diisocyanate (IPDI) and 1, 4-butanediol were carried out to modify the fiber properties. The effect of filler loading and IPDI-polyol as a coupling agent on mechanical properties, morphology, swelling behavior, thermal properties and thermal degradation were investigated. The composites were prepared by using Z-blade mixer at processing temperature 200 0C and rotor speed 50 rpm and mixed samples were then compressed by using a hydraulic hot press at the same temperature to form sheet samples composites. Generally, the results indicated that LDPE/ABS/WHF composites with IPDI-polyol as a coupling agent showed better mechanical properties and water absorption resistance than LDPE/ABS/WHF composites without IPDI-polyol. Micrograph of tensile fractured surface shows that the properties of modified fibers composites have better filler dispersion in matrix and embedded fiber into the matrix compared to unmodified fiber composites. It was also found that the modified WHF offers better thermal stability in the LDPE/ABS/WHF composites than unmodified LDPE/ABS/WHF composites.